Pengaruh Keterampilan Mengajar Guru Matematika Terhadap Prestasi Siswa - Rahmatia, Rahmatia; Azis, Azis (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
Being a teacher is not only about mastering the subject matter to be delivered, but more than that. Teachers must have quite a lot of skills to create a more effective and quality learning process. The purpose of this study was to determine the positive influence between the teaching skills of mathematics teachers on the achievement of students of SMK Negeri 2 Baubau class XI Motorcycle Department. This type of research is quantitative research with Ex Post Facto method. The population in this study were all students of SMK Negeri 2 Baubau grade XI Motorcycle Department which amounted to one class consisting of 20 students. While the sampling technique uses saturated sampling. The teacher teaching skills instrument that researchers used in this study was a questionnaire. While the achievement instrument in this study is the results of students' daily test scores. Based on the results of the study, the regression equation Y = 26.302 + 0.450X was obtained. Thus it can be concluded that there is a positive influence between the teaching skills of mathematics teachers on the achievement of students of SMK Negeri 2 Baubau class XI Motorcycle Department.